A novel switched inductor configuration for modified SEPIC DC-to-DC converter for renewable energy application - Maroti P.K.; Padmanaban S.; Blaabjerg F.; Fedk V.; Siano P.; Ramachandaramurthy V.K. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric inductors; Electric inverters; Energy conversion; Gain measurement; HVDC power transmission; DC-to-DC converters; High gain; High voltage gain; Mathematical analysis; MATLAB/ SIMULINK; Renewable energy applications; SEPIC converter; Switched inductors; DC-DC converters